An algorithmic framework for robust access control in wireless sensor networks - Benenson, Zinaida; Freiling, Felix; Kesdogan, Dogan (EWSN 2005, 2005)
If the data collected within a sensor network is valuable or should be kept confidential then security measures should protect the access to this data. We first determine security issues in the context of access control in sensor networks especially focusing on the problem of node capture, i.e., the possibility that an attacker can completely take over some of the sensor nodes. We then introduce the notion of t-robust sensor networks which can withstand capture of up to t nodes and consider three basic security concepts for such networks: (1) t-robust storage, a mechanism to securely store data within a set of sensors such that capture of any t sensors does not reveal that data to the adversary; (2) n-authentication which ensures that authentication is achieved with every uncompromised sensor in the broadcast range of a client (n denotes the number of nodes in that broadcast range); and (3) n-authorization, an authorization primitive with similar properties like n-authentication. We present a generic trobust protocol for implementing access control using these primitives. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IMMD.lehrst.analgo